Effects of Protective American Football Headgear on Peripheral Vision Reaction Time and Visual Target Detection in Division I NCAA Football Players - Rachel A. Miller; Rebecca R. Rogers; Tyler D. Williams; Mallory R. Marshall; Justin R. Moody; Robert W. Hensarling; Christopher G. Ballmann (Sports, 2019)
The purpose of this study was to examine the effects of protective football headgear on peripheral vision reaction time and visual target detection. Twenty-five Division I NCAA football players (age = 20.5 yrs ± 0.9, height = 185.9 cm ± 6.8, body mass = 99.2 kg ± 19.2, BMI = 29.6 ± 4.5) participated. In a crossover counterbalanced study design, subjects participated in one visit with three conditions: Baseline (BL) without headgear, helmet only (HO), helmet with an eye shield (HE). Subjects completed a 1-min peripheral vision reaction time test for each condition separated by 3-min recovery periods. Tests were administered using a 64 light Dynavision D2 Visuomotor board. Target detection (total hit score) was higher during BL than HO (p < 0.001) and HE (p < 0.001). Average (p < 0.001), peak (p < 0.001), minimum (p < 0.001), and median (p < 0.001) peripheral reaction times were faster during BL than HO and HE. No significant differences were observed for any measures between HO and HE conditions (p > 0.05). Findings indicate that protective football headgear impaired reaction time to peripheral visual stimuli. The addition of an eye shield to the helmet had a small non-significant effect on reaction time and target detection. These results may hold important implications in helmet design and player safety.